2018
DOI: 10.1101/272708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for a unique DNA-dependent RNA polymerase in cereal crops

Abstract: 38. CC-BY-NC-ND 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Poaceae-specific duplication of putative Pol V largest (NRPE1) and second-largest (NRPD2) subunits raises interesting questions about the assembly of multiple non-canonical polymerases in rice (Trujillo et al 2018). Zheng and colleagues recently demonstrated that NRPF1 is not redundant with NRPE1, and not required for RdDM in seedlings (Zheng et al 2021), suggesting that each paralogous largest subunit has unique function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poaceae-specific duplication of putative Pol V largest (NRPE1) and second-largest (NRPD2) subunits raises interesting questions about the assembly of multiple non-canonical polymerases in rice (Trujillo et al 2018). Zheng and colleagues recently demonstrated that NRPF1 is not redundant with NRPE1, and not required for RdDM in seedlings (Zheng et al 2021), suggesting that each paralogous largest subunit has unique function.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these two largest subunits form the catalytic center of the polymerase. In the grass family, NRPE1 and NRPD2 duplicated, giving rise to NRPF1 and NRPF2, respectively (Trujillo et al 2018). Phylogenetic analysis suggests that these paralogs have new functions, however their functions are not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future genetic analyses and artificial co-targeting strategies [60] will help dissect the complex interplay between the multiple layers of chromatin modification and non-coding RNA regulation in plants. eudicot plants [62,191]. Although the molecular and biological functions of these extra RNA polymerase subunits remain unknown, they might reinforce or even extend the RdDM machinery in species like rice, barley and maize.…”
Section: Discussionmentioning
confidence: 99%
“…Functional information residing in the sequence motif (H) adjacent to the C can influence both the frequency of methylation and the recruitment of specific methyltransferases acting upon the trinucleotide (Law & Jacobsen, ; Gouil & Baulcombe, ). The RNA‐directed DNA methylation (RdDM) pathway employs specialized plant‐specific RNA polymerases to establish DNA methylation: NRPD or POLIV, NRPE or POLV and the recently described grass‐ (Poacea) specific NRPF or POLVI (Box ) (Haag & Pikaard, ; Zhou & Law, ; Trujillo et al ., ). RNA POLYMERASE IV (POLIV) transcribes short (26–45 nucleotides) single‐stranded RNA (ssRNA) from the template/target loci.…”
Section: Establishing Dna Methylation Through the Rna‐directed Dna Mementioning
confidence: 97%